The importance of non-verbal comunication for the teaching of english to teenage students at the Catholic University of Ambato - Pérez Sornoza, Florcita Mariela (2001)
1. Comunication 2. Culture 3. Non-verbal Communication 4. Classroom Research 5. Teaching Non-verb Communication through Activities 5. Conclusions and Recommendations